Understanding the Sexual Prejudices of Sexual Orientation Minorities - Butterfuss, Reese M.; Rusten, Marta L. (My University, 2013)
Much of the sexual prejudice research has focused on understanding the prejudices and stereotypes of heterosexuals towards nonheterosexuals. Minimal research has examined the prejudices and stereotypes of nonheterosexuals. The purpose of this study was to find out the stereotypes endorsed by gay/lesbian and bisexual men and women toward heterosexual, bisexual, and gay/lesbian men and women.
Color poster with text and charts.
Keywords: LGBT community; Prejudices; Stereotypes; Posters